Evaluation of Oral Health Literacy among Midwifery Experts Working in Isfahan Health Centers - Marjan Behtti; Hajar Atarzadeh; Hajar Shekarchizadeh; Roshanak Mirzaei (Isfahan University of Medical Sciences, 2023)
The physiological changes in the mother's body during pregnancy make this group more sensitive to oral and dental diseases, which can have important effects on the health of the mother and the child. To improve the oral and dental health of the mother and the health of the baby, dental care before pregnancy and during pregnancy seems necessary. The purpose of this study was to determine the level of oral health literacy in midwifery experts working in Isfahan health centers.Materials&Methods:This research is descriptive and cross-sectional and 110 questionnaires answered by midwifery experts were selected for review in this study. The questionnaire used in this study includes two demographic questions in the field of age and work experience of midwifery experts and 20 questions about measuring oral health literacy. The data were analyzed with chi-square and Fisher's exact test (α = 0.05).Results:No relationship was observed between oral health behavioral habits and health literacy level in midwifery experts (p value = 0.449). There was no significant relationship between the oral health literacy score of midwifery experts with age (p value = -0.338, r = 0.693) and work experience (p value = -0.095, r = 0.325).Conclusion:According to this study, it can be concluded that the oral health literacy of midwifery experts is sufficient, but the need for more training to increase the updating of information of midwives in Isfahan is felt.